2010
DOI: 10.5572/kosae.2010.26.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Summer Heat Stress (Perceived Temperature) and Daily Excess Mortality in Seoul during 1991~2005

Abstract: This study investigates the relationship between daily mortality and heat stress in Seoul, using perceived temperatures (PT) derived from a heat budget model. During the summer season, observed PT intensity showed the biggest magnitude of summer heat stress from the middle 10 days of July to the first 10 days of August. The elderly (65 and above) were found to be the most vulnerable to heat stress. The threshold PT, with a significant increase in excess mortality, was 38� C. No time lagged effect was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Several previous studies used AT [ 10 , 20 ] and PT [ 13 ] as a high temperature indicator with the assumption that they are better indicators of excess morality because they consider health-related weather variables as well as the temperature. However, our main findings indicate that PT and AT, composite weather indexes, do not always act as the best predictors for an assessment of heat-related mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several previous studies used AT [ 10 , 20 ] and PT [ 13 ] as a high temperature indicator with the assumption that they are better indicators of excess morality because they consider health-related weather variables as well as the temperature. However, our main findings indicate that PT and AT, composite weather indexes, do not always act as the best predictors for an assessment of heat-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…And the mean, minimum, and maximum temperature; the mean, minimum, and maximum AT; and the mean, minimum, and maximum PT were compared. We did not include the heat index because previous studies concluded that the heat index was not a good predictor for mortality in Korea [ 13 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the extreme heat of day and night can cause the heat‐related illnesses in Korea (Choi & Kwon, ; Kim et al, ; Park et al, ). It is known that the perceived temperature, which is associated with heat stress, is highly correlated with mortality (Lee et al, , ). Meanwhile, the damage of the TN also exists.…”
Section: Introductionmentioning
confidence: 99%